Personal Selling Stress And Coping Strategies Among Sales Executives: A Case Of Selected Insurance Companies In Ghana (International Journal of Scientific Research and Management (IJSRM), 2016)
The changes in the business environment in Ghana have considerably made it possible for more qualified sales executives totarget the working class for their incomes and this has resulted in job stress of sales executives. In light of this, the study was toassess work stress among sales executives in Ghana. The main objectives of the study were to identify the causes of stress amongsales executives, the coping strategies they adopt to contain the stress and to determine the gender differences in coping strategiesof sales executive. The research design for the study was descriptive survey. Questionnaire was employed to collect data from 80sales executives from four insurance companies in Eastern Region of Ghana. Purposive sampling technique was used in selectingthe respondents for the study. The study revealed that sales job is stressful in insurance companies. The study again showed thatthere is poor demand for insurance products as a result of keen competition. The study further revealed that positive relationshipswith colleagues and family members help reduce stress in insurance oriented jobs. Again, the study indicated that salesmen areable to cope with sales job stress better than their female counterparts. Therefore, for sales executives to reduce stress,management should redesign sales job tasks in terms of difficulty to enhance the achievement of objectives and to make theinsurance job more interesting.